Comparison of 2 Diagnostic Criteria for the Behavioral Variant of Frontotemporal Dementia. (August 2013) - Costa, Sónia; Suárez-Calvet, Marc; Antón, Sofia; Dols-Icardo, Oriol; Clarimón, Jordi; Alcolea, Daniel; Fortea, Juan; Carmona, María; Sala, Isabel; Sánchez-Saudinós, M. Belén; Blesa, Rafael; Lleó, Alberto
Objectives: The aim of this study was to compare the applicability of the 1998 consensus diagnostic criteria for the behavioral variant of frontotemporal dementia (bvFTD) with the recently proposed diagnostic criteria of the International bvFTD Criteria Consortium (FTDC). Methods: We reviewed each individual item in the 1998 and FTDC criteria in 30 patients with bvFTD followed in a memory clinic (including 2 with the C9orf72 gene repeat expansion). Results: All patients fulfilled the FTDC criteria (40% possible, 60% probable bvFTD) but only 66.7% fulfilled the 1998 criteria. One of the C9orf72 expansion carriers did not fulfill the 1998 criteria. This discordance was always due to the presence of exclusion features in the 1998 criteria, the most common being spatial disorientation and early severe amnesia. Conclusion: The new FTDC criteria are less restrictive and hence more sensitive for the diagnosis of bvFTD.